RESPONSIBILITY OF THE MARINE HULL AND MACHINERY COMPANY OF INSURED CLAIMS - Tri Mulyatno Budhi Hartanto (International Journal of Law and Legal Ethics, 2020)
Risks at sea can occur in any form and anywhere, for example ships sinking due to collisions, bad weather at sea, cargo decaying, damaged, lost or stolen, or other events that cause trading activities carried by ships to run smoothly and result in losses / lost profits for all parties. To protect the parties in trading activities by sea from a variety of possible events that can be detrimental / result in loss of profits, there needs to be a mechanism or means to divert the risk of the parties' losses from damage / loss of goods or physical defects / loss of life resulting from operations merchant ships at sea. Means of transferring the risk through insurance. This research is a qualitative descriptive study. The research approach used in this paper is the statute approach. The statute approach is carried out by examining all laws and regulations relating to the legal issues being addressed. The research conducted is aimed more at the approach to laws and regulations associated with the problem of Responsibility of the Marine Hull and Macinery Company of Insured Claims. Data Analysis Techniques Data analysis techniques used for this study are deductive analysis methods, namely the method of data analysis that began from the general postulates of certain postulates and paradigms as a base for starting conclusions. Liability of the guarantor for claims in Marine Hull and Machinery insurance is to provide protection for the rights of the insured that has been promised at the time of insurance closure that has been made with a deed that is an insurance policy or in other words the guarantor is responsible for providing compensation to him due to an expected loss, damage or loss of profit, which may be he will suffer because of an unspecified event based on the policy agreed upon as long as the policy is made meeting the basic conditions of the agreement and fulfilling the principles of the insurance agreement.